Global English and New Sociocultural Concepts in Armenia - Yernjakyan, Nvard (Armenian Folia Anglistika, 2005)
The political, economic and social changes in Armenia have their direct impact on linguistic realities and studies in the field of linguistics. The article views the official and popular equivalents of the English words and word combinations in the language of public management as an influence of the global English which predominantly is the result of the manifold activities of international organizations.